The Principal's Strategy for Implementing Online Learning During the COVID-19 Pandemic at Xaverius Baturaja High School - Arisanti Siregar, Fitria; ., Syarwani; ., Mahasir (KnE Social Sciences, 2022)
This study determines and describes the role of the principal, the obstacles faced, and the strategies used by them for implementing the distance learning process in schools during the COVID-19 pandemic. A qualitative approach with a descriptive method was used in this research. Data collection techniques included observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and verification. The subjects of this study were principals, vice principals, and teachers of the Xaverius Baturaja High school. The results show that the role of the principal in implementing the online learning process has been crucial and, to an extent, effective. However, a few obstacles were noted, such as students experiencing Internet network difficulties – either due to the location of their residence or having no access to cell phones/tablets – and the lack of teachers’ ability to utilize technology for distance learning. The strategies used by the school’s principal for implementing distance learning were developing teachers’ teaching skills through a teachers’ conference organized by YXP and the government, optimizing the school’s infrastructure, supervising teachers, collaborating with parents and society, and conducting visiting teacher activities. Keywords: principal strategy, implementation of learning, COVID-19